Interferência da inoculação de Nitrospirillum amazonense na capacidade competitiva de mudas pré-brotadas de cana-de-açúcar e toxicidade de herbicidas à bactéria - Jonck, Luana Carolina Gomes (2025)
Inoculation with Nitrospirillum amazonense promotes biological nitrogen fixation (BNF) and phytohormone production, which can influence the competitiveness of sugarcane pre-sprouted seedlings (PSS) against weeds. However, pre-emergence herbicides may be toxic to bacterial cells. Therefore, the objective of this study was to evaluate the impact of inoculation with Aprinza (N. amazonense) on the competitiveness of sugarcane PSS, as well as the effect of weed competition on the rhizosphere microbiota, and to assess the toxicity of pre-emergence herbicides to bacterial cells. The competitiveness of sugarcane PSS was evaluated in a completely randomized design (CRD) in a 4×2 factorial arrangement. Three weed species (Merremia aegyptia, Urochloa decumbens, and Cyperus rotundus) were assessed at four densities (10, 20, 40, and 80 plants/m²), coexisting with PSS in the presence or absence of inoculation with N. amazonense, in addition to controls (PSS only, with and without inoculation). At 90 days after transplanting (DAT), seedlings were evaluated for height (cm), leaf area (cm²), shoot dry biomass (g), and root dry biomass (g). Also at 90 DAT, rhizospheric soil was analyzed for bacterial and fungal diversity through soil metataxonomic analysis, using DNA extraction and sequencing targeting the bacterial 16S rDNA and fungal ITS intergenic regions. Microbial activity was assessed by measuring the activity of β-glucosidase and arylsulfatase enzymes using the p-nitrophenol quantification method. To evaluate herbicide toxicity to N. amazonense, four in vitro assays were conducted. In the first assay, nine pre-emergence herbicides registered for sugarcane (clomazone, imazapic, tebuthiuron, indaziflam, S-metolachlor, metribuzin, isoxaflutole, sulfentrazone, and flumioxazin) were assessed for their minimum inhibitory concentration (MIC). Herbicides were tested at five doses corresponding to 1/4, 1/2, 1, 1.5, and 2 times the commercial dose (CD), along with a control treatment without herbicide. In the second assay, the resistance of N. amazonense to the application of the same herbicides in soil was evaluated by quantifying the Most Probable Number (MPN) of colony-forming units (CFU) of N. amazonense per gram of soil using the McCrady table. The third assay assessed the impact of herbicides on the bacterium's BNF capacity in nitrogen-free semi-solid NFb medium using the semi-micro Kjeldahl digestion method. Lastly, the fourth assay examined the effect of herbicides on indole-3-acetic acid (IAA) production by the bacterium. Bacterial cells were analyzed by the colorimetric method using the Salkowski reagent. Inoculation with N. amazonense led to increases only in the height of PSS under competition with U. decumbens. A significant interaction between inoculation and plant density was observed only for the leaf area parameter in PSS competing with M. aegyptia. Inoculation induced a negative correlation between increasing M. aegyptia density and a reduction in seedling leaf area. The presence of U. decumbens, M. aegyptia, and C. rotundus caused reductions in the height, shoot biomass, and leaf area of PSS, regardless of inoculation with N. amazonense. Microbial inoculation and weed competition did not significantly alter the structure of the bacterial and fungal communities or the enzymatic activity of the rhizospheric soil of PSS. However, taxa attributed to the genus Nitrospirillum (classified as Azospirillum in the reference database used) were found only in the inoculated PSS treatments and inoculated PSS under competition with U. decumbens. Different herbicide molecules elicited distinct responses in the survival and functional activity of N. amazonense. Indaziflam, metribuzin, S-metolachlor, and sulfentrazone did not affect bacterial survival or functionality, but promoted increased cell growth and stimulated IAA production and/or BNF. Isoxaflutole stimulated bacterial growth at sublethal doses; however, it exhibited inhibitory effects at commercial application rates, while not interfering with IAA production or BNF capacity. Clomazone and imazapic, when added to the culture medium, reduced bacterial growth but did not affect survival in soil, and increased IAA production and BNF. Flumioxazin and tebuthiuron stimulated bacterial growth and BNF but reduced IAA production. Under the conditions of the present study, it can be concluded that although N. amazonense shows potential, inoculation was not able to mitigate the adverse effects of weed competition on the growth of pre-sprouted seedlings, suggesting that methodological adjustments or complementary practices are necessary to increase its efficacy. Furthermore, our results highlight the importance of a careful selection of herbicides, considering not only their acute toxicity but also their differential effects on essential microbial processes, thereby favoring synergistic strategies that combine effective weed control with the use of microbial inoculants.